Nanosilver on nanostructured silica Antibacterial activity and Ag surface area - Sotiriou, Georgios A (Chemical engineering journal (Lausanne, Switzerland : 1996), 2011)
Nanosilver is one of the first nanomaterials to be closely monitored by regulatory agencies worldwide motivating research to better understand the relationship between Ag characteristics and antibacterial activity. Nanosilver immobilized on nanostructured silica facilitates such investigations as the SiO2 support hinders the growth of nanosilver during its synthesis and, most importantly, its flocculation in bacterial suspensions. Here, such composite Ag/silica nanoparticles were made by flame spray pyrolysis of appropriate solutions of Ag-acetate or Ag-nitrate and hexamethyldisiloxane or tetraethylorthosilicate in ethanol, propanol, diethylene glucolmonobutyl ether, acetonitrile or ethylhexanoic acid. The effect of solution composition on nanosilver characteristics and antibacterial activity against the Gram negative Escherichia coli was investigated by monitoring their recombinantly synthesized green fluorescent protein. Suspensions with identical Ag mass concentration exhibited drastically different antibacterial activity pointing out that the nanosilver surface area concentration rather than its mass or molar or number concentration determine best its antibacterial activity. Nanosilver made from Ag-acetate showed a unimodal size distribution, while that made from inexpensive Ag-nitrate exhibited a bimodal one. Regardless of precursor composition or nanosilver size distribution, the antibacterial activity of nanosilver was correlated best with its surface area concentration in solution